The effectiveness of coconut-dreg-based mudballs in kitchen wastewater treatment from restaurants and poultry shops - Maklen, Nur Sabrina; Shafie, Farah Ayuni; Abdullah, Norhidayah; Aziz, Saidatul Afzan Abdul; Ishak, Noriza (Healthscope: The Official Research Book of Faculty of Health Sciences, UiTM, 2025)
This study investigates the effectiveness of coconut-dreg-based mudballs as a sustainable and cost-effective solution for treating kitchen wastewater from restaurant and poultry shop sources. Kitchen wastewater, characterized by its high organic load and potential pathogen content, poses significant environmental and public health risks if not adequately treated. Leveraging the principles of circular economy and sustainable waste management, coconut dregs, a by-product of the food industry, are harnessed for their potential in bioaugmentation to develop mudballs for wastewater treatment. Mudballs is a well-known biological treatment method for wastewater. Laboratory experiments were conducted to assess the removal efficiency of pollutants, including pH, dissolved oxygen (DO), turbidity, chemical oxygen demand (COD), and ammoniacal nitrogen, comparing the performance of coconut-dreg-based mudballs with conventional mudballs. Coconut- dreg-based mudballs demonstrated significant turbidity reduction (91.33%), COD reduction (84.84%), and effective ammoniacal nitrogen reduction (89.13%), particularly in kitchen wastewater from restaurants. The alkaline and fibrous nature of coconut dregs were identified as the key factors contributing to these favourable results. The enhanced effectiveness of coconut-dreg-based mudballs highlights their viability as a cost-effective and environmentally friendly alternative for kitchen wastewater treatment.